Peningkatan pengetahuan dan perilaku peduli lingkungan melalui edukasi pemilahan sampah di SD Negeri 04 Sam Sam - Jamilah, Putri; Ryandi, Muhammad; Nabilla, Sarah (Penamas: Journal of Community Service, 2025)
Awareness of the importance of protecting the environment needs to be instilled from an early age. Environmental education in schools plays a vital role in shaping students' character and habits, but is often limited to theoretical concepts in the classroom. This community service activity aims to describe the role of KKN students in instilling values of environmental care among students of SD Negeri 04 Sam Sam. This activity was attended by approximately 30 fourth-grade students from SD Negeri 04 Sam Sam, who actively participated in each stage of the program. The program included educational outreach on types of waste and their dangers, as well as practical actions for sorting waste by type. The results of the activity showed a significant increase in students' knowledge and behaviour related to environmental cleanliness. Students were able to distinguish between organic and inorganic waste and showed high enthusiasm for cleanliness activities at school. The presence of KKN students as facilitators and role models proved effective in creating a fun, interactive learning atmosphere, thereby enhancing the effectiveness of the environmental awareness education process.